Socialist Endeavors, Fist Presses and Pen Wars: Literacy practices of early Finnish migrants in Australia - Anne Heimo (Umeå university, 2022)
This article is about the short-lived history of Finnish socialist societies in Australia in the first decades of the twentieth century. At the same time, it tells of the first Finnish community in Australia,Finbury, and how the members of this small community represented their life on the pages of Orpo (Orphan) in their own words and fortheir own needs. Orpo was a hand-written and single copy newspaper published by the “Asiainedustusseura Erakko” (“The Hermit Society for the Promotion of Affairs”) from 1902 to 1904. The society was established to advance the cultural, intellectual and social wellbeing of all of the members of their small community. Orpo offers a rare opportunity to study both individual and collective experiences of settling into a new country from the point of view of the migrants themselves as well as the literacy practices of these early Finnish migrants.
Reading and Writing from Below: Exploring the Margins of Modernity.